Pentagamavunon-0 (PGV-0) Enhance Cytotoxic Effect of Doxorubicin through Increasing of Apoptosis, Senescence and ROS Level on Triple Negative Breast Cancer 4T1 - Ismanurrahman Hadi; Riris Istighfari Jenie; Edy Meiyanto (Indonesian Society for Cancer Chemoprevention, 2020)
TNBC, one of the sub type of breast cancers was widely known with high tumorigenic and poor prognosis than others. The development of combination agent (co-chemotherapy) with doxorubicin for chemotherapy of TNBC were carried out to decrease doxorubicin side effect and resistance in cancer. This present study aims to explore the co-chemotherapeutic properties of PGV-0 and investigate induction of doxorubicin on apoptosis, senescence and ROS against TNBC. 4T1 Cell line were used as a TNBC in vitro model. Cytotoxic measurement was performed using MTT assay resulting in IC50 values of 52 μM. Meanwhile, the combination of doxorubicin and PGV-0 showed synergistic effect which decreased cell viability of 4T1 better than single treatment of doxorubicin. Apoptosis analysis was performed using annexin V/PI assay indicated that the combination treatment of PGV-0 and doxorubicin increased apoptosis evidence. Senescence detection was carried out using senescence-associated-β galactosidase (SA-β-gal) assay. The results showed that a single treatment of PGV-0 induced cellular senescence and increased senescence cells in combination treatment. Moreover, DCFDA staining showed that PGV-0 increased ROS level at single treatment, whereas combination treatment increased ROS intracellular compared to the positive control of doxorubicin. Based on these results, PGV-0 has potential as a co-chemotherapeutic candidate on TNBC.Keyword: 4T1, PGV-0, Co-chemotherapy, Cytotoxic, Senescence, Apoptosis, ROS